Apuntes sobre epistemología e investigación en laenseñanza de los Estudios Sociales - Morales Zúñiga, Luis Carlos (2010)
This article examines the concept of social studies, contrasting it with the conceptual notion called didactic of social sciences, in order to observe the particularities of each category. Subsequently a sketch of epistemology applied to the field of social studies is presented, with the goal to rethink the construction of knowledge and research objects in this field. Finally we thought on the possibility of establishing directions or systematic research lines which will organize the investigation processes in the teaching of social studies.